Morphological transformation of numerical phrases into verbs in the Javanese language - Somawati, Ni Putu; Wajdi, Majid; Susanto, Budi; Udoudom, Uduak Imoh; Claridad, NF; Mohammed, LA (Journal of Language, Literature, Social and Cultural Studies, 2024)
This study explores the morphological process in the Javanese language where numerical phrases are transformed into verbs through the addition of the prefix "N-." This process is not only a linguistic phenomenon but also deeply rooted in Javanese culture and socio-religious practices. The urgency of this study lies in documenting and analysing how these transformations reflect cultural traditions, particularly the ceremonial practices observed after specific days following someone's death, such as the third, seventh, fortieth, one hundredth, and one-thousandth days. A review of previous studies shows a lack of focus on the intersection of language, culture, and religion in the transformation of numerical phrases into verbs. This study fills this gap by examining the specific phrases "telung dina" (three days), "pitung dina" (seven days), "patang puluh dina" (forty days), "satus" (one hundred), and "sewu" (one thousand), which are culturally significant in Javanese rituals, and their transformation into verbs such as "nelung dina," "mitung dina," "matang puluh dina," "nyatus," and "nyewu." The analysis demonstrates that the prefix "N-" not only verbalizes these phrases but also embodies the cultural significance of the corresponding periods, turning static expressions into action-oriented verbs that imply ceremonial activities. The conclusion emphasizes the importance of this morphological process in understanding how the Javanese language encapsulates cultural values and practices, offering new insights into the relationship between language, culture, and religion in Austronesian linguistics.